Strategi Peningkatan Kapasitas UMKM melalui Program Pemberdayaan di Wilayah Jakarta Timur - Muhammad Farhan Muzakki; Ade Maya Kartini; Belinda Febri Patricia; Edo Bagasunanda; Muhammad Syauqi Baihaqi; Nurlia Mahmudah; Rafii Marlano; Stacia Stacia; Lindawati Kartika (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
One of the means of community service in improving the economy is the Thematic Real Work Lecture at the Bogor Agricultural University (KKN-T IPB). Students play very important role in improving the community's economy through the KKN-T IPB’s programs, especially in the COVID-19 pandemic situation which results in the limitation and closure of various business sectors. This community service aims to improve the soft skills of the community in this case Small and Micro Enterprises (SMEs) so that they can remain competitive and increase the scale of their business in Jatinegara District, East Jakarta Administrative City. Methods used in this community service is by training directly in the Jatinegara District Office Hall and online through the zoom teleconference media. The training carried out (training that has been held) namely, financial recording training; product photo training, design training using Canva and Instagram; digital marketing training; food packaging training; and financial management webinars. The results of the training show that MSEs in Jatinegara District understand the material provided in each training, benefit from the training, and the training content well-suited with the business undertaken by each participant.